2019
DOI: 10.4103/ortho.ijortho_410_17
|View full text |Cite
|
Sign up to set email alerts
|

Distal Femoral Extension Osteotomy with 90° Pediatric Condylar Locking Compression Plate and Patellar Tendon Advancement for the Correction of Crouch Gait in Cerebral Palsy

Abstract: Background: Various treatment modalities are available for the correction of crouch gait, ranging from hamstring lengthening to a combination of soft-tissue and bony procedures. We report the results of distal femoral extension osteotomy (DFEO) fixed with 90° pediatric condylar locking compression plate (LCP) and patellar tendon advancement (PTA) for crouch gait in children with cerebral palsy. Materials and Methods: A total of 26 patients (52 knees) with a mean age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…There was no correlation between NC and the amount of correction, concomitant surgeries, tourniquet time, malnutrition level or emotional state. Aroojis et al [13] reported 3 transient peroneal palsies after DFEO and PTA in 52 knees. Asirwatham et al [12] reported an 8.6% rate of NC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There was no correlation between NC and the amount of correction, concomitant surgeries, tourniquet time, malnutrition level or emotional state. Aroojis et al [13] reported 3 transient peroneal palsies after DFEO and PTA in 52 knees. Asirwatham et al [12] reported an 8.6% rate of NC.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of fixed knee flexion of 10-30 degrees, DFEO was proven to be valuable in preventing and treating crouch gait [4,5,9,21]. It has been reported that combination with patellar tendon advancement might give better functional results [4][5][6]9,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distal femoral extension osteotomy (DFEO) for the treatment of patients with fixed flexion deformities associated with arthritic conditions and neuromuscular disorders is a wellestablished procedure [1][2][3].The use of 90⁰ locking plates for the correction of persistent crouch gait in pediatric cerebral palsy patients has been described with favorable results, including improved mobility, decreased flexion deformity and extensor lag, and increased muscle strength [1][2][3][4] Reported complications with this technique in cerebral palsy patients vary with modern reports ranging from less than 5% to 19% [1,3,4]. Frequent complications with use of plate fixation in DFEO include delayed union or nonunion, fixation failure, loss of correction, and neurovascular injury [2,5].…”
Section: Introductionmentioning
confidence: 99%